2013
DOI: 10.1111/iwj.12098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glutamine on wound healing

Abstract: Studies reporting the need for replacing amino acids such as glutamine (Gln), hydroxymethyl butyrate (HMB) and arginine (Arg) to accelerate wound healing are available in the literature. The primary objective of this study was to present the effects of Gln on tissue hydroxyproline (OHP) levels in wound healing. This study was conducted on 30 female Sprague Dawley rats with a mean weight of 230 ± 20 g. Secondary wounds were formed by excising 2 × 1 cm skin subcutaneous tissue on the back of the rats. The rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…[ 47 ] Also, it has been assumed that fibroblasts, a type of cell that synthesizes the extra cellular matrix and collagen which plays a critical role in wound healing, use Gln as the main energy resource for proliferation. [ 34 51 ] In addition, proline, one of the Gln metabolism products, is essential for the collagen production. Furthermore, Gln can metabolize to arginine that it can promote wound healing in pharmacological doses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] Also, it has been assumed that fibroblasts, a type of cell that synthesizes the extra cellular matrix and collagen which plays a critical role in wound healing, use Gln as the main energy resource for proliferation. [ 34 51 ] In addition, proline, one of the Gln metabolism products, is essential for the collagen production. Furthermore, Gln can metabolize to arginine that it can promote wound healing in pharmacological doses.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of a mixture of arginine, glutamine, and b-hydroxyb-methylbutyrate was also reported to decrease wound sizes at 10 and 14 d after injury (45). Administration of these same amino acids also increased hydroxyproline content in diabetic foot ulcers (46), but not in a basic science model of the same injury (47). Regardless, there is considerable variation in supplementation and wound outcomes and definitive studies are needed to determine whether or not glutamine could be used therapeutically, either alone or in combination with other amino acids, to facilitate wound healing in a clinical setting.…”
Section: Clinical and Preclinical Data Examining Nutrient Supplementamentioning
confidence: 96%
“…In a study done in 2013 by Kesici et al, whose results contrasted with those of the study just discussed, in which supplementation was associated with improved scores for wound depth and appearance, amino acid supplementation in rats was not associated with significant increases in hydroxyproline concentrations. This finding is important in identifying a potential difference in the biochemical milieu of healing wounds in diabetic patients as compared with healthy controls [9]. The second human study identified in our literature review focused on arginine supplementation in patients with diabetic foot wounds.…”
Section: Literature Review: Pilot Data In Contextmentioning
confidence: 97%
“…Glutamine is a nonessential amino acid, found in abundance in human beings. Its tissue concentrations can be diminished by more than 50% and plasma concentrations may be diminished by more than 25% after a major catabolic insult [9]. Arginine is a semiessential amino acid that becomes essential in critical illness.…”
Section: Literature Review: Pilot Data In Contextmentioning
confidence: 99%
See 1 more Smart Citation